1999
DOI: 10.1001/archinte.159.19.2349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Older Patients With Major Depression

Abstract: An exercise training program may be considered an alternative to antidepressants for treatment of depression in older persons. Although antidepressants may facilitate a more rapid initial therapeutic response than exercise, after 16 weeks of treatment exercise was equally effective in reducing depression among patients with MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
720
7
72

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,040 publications
(827 citation statements)
references
References 52 publications
28
720
7
72
Order By: Relevance
“…Some studies showed that fitness was associated with reduction of symptoms while others demonstrated reduction in symptoms without increased fitness. Blumenthal et al 24 showed that greater attendance and higher exercise intensity were related to improvements in aerobic capacity and that change in aerobic capacity was related to reductions in depressive symptoms in older adults. Three months of aerobic exercise performed in an exercise laboratory at a cumulative caloric dose consistent with public health physical activity recommendations 49 was more effective in reducing depressive symptoms and inducing remission compared to a lower total dose of exercise in young adults with major depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that fitness was associated with reduction of symptoms while others demonstrated reduction in symptoms without increased fitness. Blumenthal et al 24 showed that greater attendance and higher exercise intensity were related to improvements in aerobic capacity and that change in aerobic capacity was related to reductions in depressive symptoms in older adults. Three months of aerobic exercise performed in an exercise laboratory at a cumulative caloric dose consistent with public health physical activity recommendations 49 was more effective in reducing depressive symptoms and inducing remission compared to a lower total dose of exercise in young adults with major depression.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of lapse in Silver Sneakers attendance was 28%-55% (p<0.05) higher for depressed participants during months [15][16][17][18][19][20][21][22][23][24]. For nondepressed Silver Sneakers participants, attendance of at least 2 visits/week during Year 1 was significantly associated with lower risk of depression in Year 2 (OR=0.54; 95%CI= 0.37, 0.79; p=0.002); a similar but statistically nonsignificant association was observed for previously depressed participants (OR=0.51; 95%CI=0.26, 1.02; p=0.06).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[55] The effect of exercise on MDD has been studied in healthy adults, persons with psychiatric conditions, and older adults. [56] Across studies, exercise appears to be more beneficial than no treatment, and in some studies it has been as effective as antidepressant medication and psychotherapy for mild to moderate depression. [57] Exercise has also been associated with lower depression relapse rates compared to pharmacotherapy.…”
Section: Exercisementioning
confidence: 99%
“…[57] Exercise has also been associated with lower depression relapse rates compared to pharmacotherapy. [56,58] Moderate exercise (walking 20 minutes a day at 60% maximum heart rate) has been more effective than vigorous exercise and is associated with fewer drop outs. [59] …”
Section: Exercisementioning
confidence: 99%